Responses of diazotrophic network structure and community diversity to alfalfa-maize intercropping are soil property-dependent - Zhang, Jinglei; Wu, Bo; Wang, Guoliang; Zhang, Jinhong; Jia, Chunlin (Frontiers in Microbiology, 2024)
Intercropping and soil properties both affect soil diazotrophic communities. However, the specific effects that alfalfa-maize intercropping has on diazotrophic networks and community diversity under different soil properties remain unclear. In this study, we investigated the soil diazotrophic communities of two crop systems, alfalfa monoculture (AA) and alfalfa-maize intercropping (A/M), in two sites with similar climates but different soil properties (poor vs. average). The diazotrophic network complexity and community diversity were higher at the site with poor soil than at the site with average soil (p<0.05). Community structure also varied significantly between the sites with poor and average soil (p<0.05). This divergence was mainly due to the differences in soil nitrogen, phosphorus and organic carbon contents between the two sites. At the site with poor soil, the A/M system had lower diazotrophic diversity, lower network complexity and greater competition between diazotrophs than the AA system (p<0.05) because intercropping intensified the soil phosphorus limitation under poor soil conditions. However, in the average soil, it was the A/M system that had an altered diazotrophic structure, with an increased abundance of 11 bacterial genera and a decreased abundance of three bacterial genera (p<0.05). Our results indicated that the effects of alfalfa-maize intercropping on diazotrophic communities were soil property-dependent.